A molecular dynamics study of the thermal conductivity of graphene nanoribbons containing dispersed Stone–Thrower–Wales defects - Ng, Teng Yong (2013)
Classical molecular dynamics with the AIREBO potential is used to investigate the thermal conductivity of both zigzag and armchair graphene nanoribbons possessing different densities of Stone–Thrower–Wales (STW) defects. Our results indicate that the presence of the defects can decrease thermal conductivity by more than 50%. The larger the defect density, the lower the conductivity, with the decrease significantly higher in zigzag than in armchair nanoribbons for all defect densities. The effect of STW defects in the temperature range 100–600 K was also determined. Our results showed the same trends in thermal conductivity decreases at all temperatures. However, for higher defect densities there was less variation in thermal conductivity at different temperatures.